Development of Pāḷi Based on Epigraphical Evidence from the Bagan Era - Lwin, Phyu Mar (Journal of International Buddhist Studies, 2025)
Pāḷi is regarded as the sacred language of Theravāda Buddhism and holds great significance for Theravādins, serving as the principal language for preserving and transmitting the teachings of the Buddha. The Bagan kingdom (11th to 13th century) in present-day Myanmar is widely recognized as a golden age of Buddhist culture, evidenced by the enduring presence of ancient temples, murals, and an extensive corpus of stone inscriptions. This article aims to investigate the profound impact of the Pāḷi language on the intellectual, religious, and social life of Bagan society. The study draws upon a wide range of both primary and secondary sources, including donative inscriptions, Burmese chronicles, epigraphic evidence, and the works of modern scholars. It employs historical and textual analysis to reveal the development of both Pāḷi and Theravāda Buddhism in ancient Bagan after the 11th century. The findings demonstrate that Pāḷi was not only used for religious purposes but also functioned as an indicator of prestige, particularly among the royal elite and learned monks. This study highlights how Pāḷi played a crucial role in shaping Bagan society and in promoting the wider spread of Buddhism. By focusing on the Bagan kingdom, this research contributes to the broader discussion on the relationship between language, religion, and culture in pre-modern Southeast Asia.